3D Printing in Medicine : A Practical Guide for Medical Professionals - Rybicki, Frank J.; Grant, Gerald T. (Springer International Publishing : Imprint: Springer, 2017)
This book describes the fundamentals of three-dimensional (3D) printing, addresses the practical aspects of establishing a 3D printing service in a medical facility, and explains the enormous potential value of rendering images as 3D printed models capable of providing tactile feedback and tangible information on both anatomic and pathologic states. Individual chapters also focus on selected areas of applications for 3D printing, including musculoskeletal, craniomaxillofacial, cardiovascular, and neurosurgery applications. Challenges and opportunities related to training, materials and equipment, and guidelines are addressed, and the overall costs of a 3D printing lab and the balancing of these costs against clinical benefits are discussed. Radiologists, surgeons, and other physicians will find this book to be a rich source of information on the practicalities and expanding medical applications of 3D printing.
Keywords: Medicine.; Radiology.; Neurosurgery.; Surgery.; elektronické knihy; electronic books